Sacred Groves of Barjora, Chhatna and Saltora Blocks of Bankura District, West Bengal - Mitra, Bulganin; Das, Priyanka; Ghosh, Sujit; Mishra, Purnendu (Indian Forester, 2015)
A total of 17 sacred groves were identified from Barjora (7), Saltora (7) and Chhatna (3) blocks of Bankura district. The largest sacred grove was reported with 0.4891 km2 at Kathia Babar Ashram in Barjora block. Total 58 trees were recorded from these three blocks of which 51 scientifically identified. Among them, 12 are important for their timber value, 16 for their food value, 17 having medicinal properties, 6 ornamental and 3 as sacred trees.